The answer is the value of 'x' that makes your statement true.
It's usually called the 'solution'.
Here's how to find it:
Write the statement:
4x + 3 = 2x + 11
Subtract 3 from each side:
4x = 2x + 8
Subtract 2x from each side:
2x = 8
Divide each side by 2:
x = 4
That's the answer. '4' is the only number you can plug in place of 'x'
that makes the statement true.
Chat with our AI personalities
2x + 33 = 4x + 11 -11 -11 2x + 22 = 4x -2x -2x 22 = 4x Divide each side by 4 x = 5.5
4x - 7 = 2x + 15 4x = 2x +222x = 22x = 11
7
4x + 2 + 2x - 2x = 14 4x = 14 - 2 4x = 12 x = 3
4x - 5 + 2x = 37